2020
DOI: 10.3389/fevo.2020.580725
|View full text |Cite
|
Sign up to set email alerts
|

Warmer April Temperatures on Breeding Grounds Promote Earlier Nesting in a Long-Distance Migratory Bird, the Prothonotary Warbler

Abstract: Global climate change and warming are altering hemispheric and local weather patterns. Altered weather patterns have great potential to affect the phenology of life history events, such as the initiation of breeding in organisms that reproduce seasonally. Long-distance migratory birds may be particularly challenged by changes in local weather on breeding grounds because they arrive from distant locations and must commence breeding when conditions are appropriate. Here we explore the effects of local temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 96 publications
(152 reference statements)
1
8
0
Order By: Relevance
“…There is, though, evidence of long-distance migrants adjusting the timing of nest initiation relative to breeding grounds temperature (Hoover & Schelsky, 2020) and relative to the snow conditions on the spring migratory path (Oliver et al, 2020). While our models for Bobolinks, a long-distance migrant, may be consistent with projections for other long-distance migrants (Miller-Rushing et al, 2008), to adjust the timing of their migration to respond to climatic-induced phenological changes (Pulido & Widmer, 2005).…”
Section: Discussionsupporting
confidence: 51%
“…There is, though, evidence of long-distance migrants adjusting the timing of nest initiation relative to breeding grounds temperature (Hoover & Schelsky, 2020) and relative to the snow conditions on the spring migratory path (Oliver et al, 2020). While our models for Bobolinks, a long-distance migrant, may be consistent with projections for other long-distance migrants (Miller-Rushing et al, 2008), to adjust the timing of their migration to respond to climatic-induced phenological changes (Pulido & Widmer, 2005).…”
Section: Discussionsupporting
confidence: 51%
“…Recent literature reflects that climate-driven adaptations in breeding phenology are evident in several songbird species in that they advance the onset of breeding in warmer springs (Kluen et al 2011, Fossøy et al 2015, Bründl et al 2020, Hoover & Schelsky 2020, Shipley et al 2020, Nicolau et al 2021. The arrival of migrants at the breeding grounds is strictly connected to their migration schedule (Schmaljohann 2019), bringing an additional challenge to the successful timing of life-history events and determining the ability to adjust lay date to the local green-up (Low et al 2019, Amélineau et al 2021, Lamarre et al 2021, Sander et al 2021.…”
mentioning
confidence: 99%
“…, Tøttrup et al, 2012 ; Aloni, Markman & Ziv, 2019 ). The gradually warmer spring season in the northern hemisphere favours the early breeding of migrants ( Ouwehand & Both, 2017 ; Hoover & Schelsky, 2020 ). Our results showed that climate changes at remote wintering grounds and at stopover sites are important drivers of changes in the arrival timing of migrants in Europe.…”
Section: Discussionmentioning
confidence: 99%